Aerodynamics and aeroelastic performance of a rigid-frame bridge with a bluff body girder subjected to short-rise-time gusts. (15th July 2022) - Dong, Xu; Zhao, Lin; Cui, Wei; Peng, Yongjun; Ge, Yaojun
Highlights: Multiple-fan active control wind tunnel tests were performed to investigate the wind effects of a long-span rigid-frame bridge subjected to short-rise-time gusts. The gust parameters in mountainous areas have significant impacts on the rigid-frame bridge. The occurrence of the impact effect is related to the gust acceleration. The flange slab has better mitigating effects for the impact of gusts on the rigid-frame bridge with bluff body cross section. Abstract: Short-rise-time gusts in mountainous areas are extreme winds with the characteristics of rapidly varying wind speeds and directions, strong suddenness, and large angles of attack. Currently, studies on long-span bridges under short-rise-time gusts in mountainous areas, especially experimental studies, are limited. In this study, a typical long-span rigid-frame bridge with a bluff body girder located in a mountainous area suffering from frequent gusts was selected. Corresponding sectional and full aeroelastic model tests in a multiple-fan active control wind tunnel were performed to investigate the aerodynamic forces and wind-induced responses under strong gusts. Two aerodynamic measures (i.e., flange slab and stabilizing plate) were applied to mitigate the impact of gusts on the studied bridge. Moreover, numerical simulation analysis was also carried out to investigate the effects of gusts on the wind-induced stresses. The experimental results demonstrated that the gust parameters significantly affect the aerodynamic forces and wind-induced responses of the long-span rigid-frame bridge, especially under construction, although this type of bridge usually shows less wind-related sensitivity under normal monsoon climates. Furthermore, the proposed aerodynamic measures effectively mitigated the displacement responses of the studied bridge subjected to gusts in mountainous areas. This investigation can provide a more comprehensive understanding of the aerodynamics and aeroelastic performance of similar bridges under gusty conditions.